Cultural context adaptions of children's literature : A case study of The joining - Salama, Sulaiman Abdullah (My University, 2008)
This research report is concerned with translation in which culture plays a major role, and examines the issues involved in translating for a specific audience – in this case Arabic-speaking Moslem children in Egypt. Translation is firstly discussed in a broader context, demonstrating that translation needs to be understood either as “rewriting” or “cultural textualisation” (Snell-Hornby, 1997:123). Secondly, the translation of children’s literature is discussed as a type of translation operating through an encounter with both culture and linguistics. Overlaps between language and culture are located and the importance of contextual adaptation is emphasised in relation to solutions proposed for addressing the cultural problems raised in the translation of Peter Slingsby’s The Joining for Egyptian children. In conclusion, suggestions are made concerning translation as adaptation in the form of possible guidelines for future translators of children’s literature into Arabic.
Keywords: translation; Egyptian children; “rewriting”; “cultural textualisation”; Arabic-speaking Moslem children